Analisa Pengaruh Brand Image dan Brand Awareness Terhadap Purchase Intention Kawasaki Ninja 250Fi - Dillon Orlando (Jurnal Strategi Pemasaran, 2015)
Indonesian society lifestyle of motorcycle sport has begun to change, with an increase in demand for motor sport is happening because of the shift of the function of the motorcycle. At first motorcycle only used as a means of transportation only. But now, especially motorcycle motor sport regarded as a lifestyle. Business competition motorcycle sport in Indonesia is getting tougher by the presence of many competitors begin launching new products. This study was carried using a questionnaire distributed directly to the object of study is all purchasers and prospective purchasers of Kawasaki Ninja motorcycles 250Fi to determine whether Kawasaki Ninja 250Fi brand image and public awareness about the brand Kawasaki Ninja 250Fi affect consumer buying interest.                                                                                                                                                                                                                                                                                                   Keyword :  Brand Image, Brand Awareness, Purchase intention.